"I'm a man of this time": Categories of Sin and the Shadow of Dante in Cormac McCarthy's No Country for Old Men. (September 2019) - Griffis, Rachel B.
Criticism on the nature of evil in Cormac McCarthy's No Country for Old Men (2005) has acknowledged the precarious moral position of Sheriff Bell, often creating sympathy for the character who resigns at a crucial time. My article argues that the novel's literary ancestor, Dante's Inferno, offers a way of reading this novel through categorizing the sins of the three main characters: Moss, Bell, and Chigurh. This categorization suggests not only that Bell is guilty of acedia, one of the seven deadly sins, but also that this particular sin elucidates the sheriff's meaning when he calls himself "a man of this time." Although more noticeable sins, such as Moss's impulsive theft or Chigurh's disciplined treachery, drive the plot and captivate readers, Sheriff Bell's acedia is the prevailing danger to morality in the novel.